الدور السياسي والعسكري للقائد حمه لخضر السوفي في المنطقة الأولى 1954-1955م - قسيبه, رشيد (جامعة الوادي - University of Eloued, 2022)
يتعرض هذا المقال إلى دور القائد السوفي حمه لخضر أثناء الثورة التحريرية المباركة 1954م-1962م في المنطقة الأولى (أوراس النمامشة) خلال عامها الأول. ويهدف هذا المقال إلى تسليط الضوء على هذا الدور سياسيا، وعسكريا، وذلك من خلال أهم المعارك التي قادها هناك أو شارك فيها، وكذلك أهم الاجتماعات والمؤتمرات التنظيمية التي كان مشاركا فيها. This article examines the role of the Soviet leader Hama Lakhdar during the blessed liberation revolution 1954-1962 in the first region (Uras alNammasheh) during its first year. This article aims to shed light on this political and military role, through the most important battles he led there or participated in, as well as the most important organizational meetings and conferences in which he was a participant.
مقال
Keywords: حمه لخضر؛ الثورة؛ فرنسا؛ وادي سوف؛ المنطقة الأولى; Hama Lakhdar; revolution; France; Valley will; first region